Exploration of Client Profile and Clinical Outcome in a University Psychology Clinic. (14th June 2016) - Brunnbauer, Lynette; Simpson, Susan; Balfour, Cathy
Abstract : Objective: The main aim of this project was to provide a client profile and to evaluate effectiveness of therapy as provided by trainees in a university‐based psychology clinic setting. Method: The participants included face‐to‐face ( n = 82) and video‐therapy ( n = 20) adult clients of the University of South Australia Psychology Clinic at Magill Campus who attended the clinic between March 2011 and August 2013. A mixed design was used to evaluate treatment effectiveness. Psychological distress was measured using the Depression, Anxiety, and Stress Scales (DASS‐21) and Clinical Outcomes in Routine Evaluation (CORE‐10). Results: Scores in the CORE‐10 indicated that the clients' distress levels significantly decreased between pre‐ and post‐treatment; however, this was not dependent on therapy completion or dropout. Unemployment status was the only factor to significantly predict therapy dropout. Conclusion: In summary, results suggest that trainees gained experience with a wide range of client groups and that therapy provided by trainees was effective.